Inequality trends and their determinants: Latin America over 1990 - 2010 - Giovanni Andrea Cornia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The paper reviews the steady and widespread decline in income inequality which has taken place in most of Latin America over 2002-10 and which - if continued for another 2-3 years - would reduce the average regional income inequality to pre-liberalization levels. The paper then focuses on the factors, which may explain such inequality decline. A review of the literature and an econometric test indicate that a few complementary factors played an important role in this regard, including a drop in the skill premium following a rapid expansion of secondary education, and the adoption of a new development model by a growing number of left-of-centre governments which emphasizes fiscally-prudent but more equitable macroeconomic, tax, social expenditure and labour policies. For the region as a whole, improvements in terms of trade, migrant remittances, FDI and world growth playeda less important role than expected although their impact was perceptible in countries where such transactions were sizeable.
Keywords: D31; E6; H53; I28; I38; 330; income inequality; human capital inequality; policy regimes; external conditions; Latin America; Einkommensverteilung; Gini-Koeffizient; Lateinamerika